Implementation of shunt active power filter using source voltage and source current detection - Khruathep U. (2014)
This paper presents the implementation of shunt active power filter using source voltage and source current detection. The harmonic current and reactive power compensation of shunt active power filter controller is based on the digital signal processing (DSP) to control its operation. First, the signal quality of the designed prototype was tested with the simulation program. Then, the prototype for experiment has been setup for verifying the performance of system. It was found that reactive power could be compensated and harmonic current could be reduced, compared to the results of an active power filter with the load current detection. Since the source current detection used less controlling devices and its structure was simple, so it is more attractive. ©2008 IEEE.